Current Application Status and Trends in Paravertebral Block for Thoracic Surgery: A 2004–2024 Bibliometric Analysis - Fu, Yanhong; Su, Jiansheng; Wang, Min (Current Journal of Applied Science and Technology, 2025)
Aims: To elucidate the current application status and research trends of paravertebral block (PVB) regional anesthesia in thoracic surgery. Methodology: Using bibliometric methods, we analyzed 931 publications from Web of Science (2004-2024) with CiteSpace 6.2.R4 to map knowledge networks and evolving trends in paravertebral block for thoracic surgery. Visual knowledge mapping was employed to identify core researchers, research hotspots, and keyword clustering in thoracic PVB applications. Results: Research output demonstrated significant growth over the past decade. Visualization analysis reveals that Canada and the United States dominated the field's intellectual development. While inter-institutional collaboration was active, overall research cohesion remained suboptimal. PVB research primarily focused on pain management and anesthesia protocol optimization, with high-centrality keywords including pain, anesthesia, postoperative pain, surgery and analgesia. Emerging trends revealed a shift from traditional agent toward minimally invasive techniques and novel nerve blocks. Conclusion: PVB exhibits significant analgesic efficacy in thoracic procedures. Future research prioritizes continuous paravertebral block and multimodal analgesia protocols. PVB holds substantial promise for postoperative analgesia and enhanced recovery pathways, with AI-assisted protocols potentially optimizing clinical implementation. Strengthening multinational and cross-institutional collaboration is essential to advance research synergy.